Effect of area on color harmony in simulated interiors - ODABAŞIOĞLU, SEDEN (WILEY, 2020)
The main aim of this study is to examine the effect of area on color harmony in simulated interior spaces. The secondary aim of the study is to investigate how the term color harmony is defined and the link between color harmony and related terms used to define it. These terms can explain why a color scheme is evaluated as harmonious. Four sets of three-color combinations created by using the hues red, blue, yellow, green, purple, and orange were studied in a simulated office interior emphasizing different proportional use of each color. Firstly, participants evaluated harmony content of the images. Secondly, they evaluated each image regarding the terms related to color harmony. Findings indicated that area had an effect on color harmony for two of the color combinations (warm & cool). However, there were no strong but rather moderate and weak correlations between color harmony and the terms.
Keywords: color harmony; experimental color harmony; simulated interior; three-color combination; SPATIAL BALANCE; LAWS; PREFERENCE; EMOTION; LIGHT; HUE